2020
DOI: 10.1182/bloodadvances.2020002184
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation after prior targeted therapy for high-risk chronic lymphocytic leukemia

Abstract: Allogeneic hematopoietic cell transplantation (alloHCT) can cure previously treated high-risk chronic lymphocytic leukemia (CLL) patients if they are suitable for transplant through the graft-versus-leukemia effect. However, since the emergence of targeted therapies, the role of alloHCT for high-risk CLL is less clear. To address this question, we evaluated 108 high-risk CLL patients who underwent alloHCT from 2010 to 2018. Thirty patients from the period of 2013 to 2018 received targeted therapy prior to allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
(62 reference statements)
1
23
0
Order By: Relevance
“…A recent singlecenter retrospective analysis of 108 patients with high-risk CLL, among whom 30 had received a novel agent before receiving HSCT, suggested favorable outcomes for patients who received previous novel therapy with 3-year PFS and OS of 72% and 87%, respectively, vs 58% and 69%, respectively, for patients who received only chemoimmunotherapy, but these differences were not statistically significant (P 5 .3 and P 5 .22, respectively). 9 Taken together, these findings and ours suggest that exposure to novel agents before HSCT does not have a negative impact on outcomes and perhaps might be advantageous. Data from larger registries are needed to more definitely answer this question.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A recent singlecenter retrospective analysis of 108 patients with high-risk CLL, among whom 30 had received a novel agent before receiving HSCT, suggested favorable outcomes for patients who received previous novel therapy with 3-year PFS and OS of 72% and 87%, respectively, vs 58% and 69%, respectively, for patients who received only chemoimmunotherapy, but these differences were not statistically significant (P 5 .3 and P 5 .22, respectively). 9 Taken together, these findings and ours suggest that exposure to novel agents before HSCT does not have a negative impact on outcomes and perhaps might be advantageous. Data from larger registries are needed to more definitely answer this question.…”
Section: Discussionsupporting
confidence: 67%
“…6 However, few studies have investigated the possible impact of previous exposure to these novel agents on HSCT outcomes. [7][8][9] With this study, we aimed to help further determine the impact of exposure to novel agents on post-HSCT outcomes in patients with CLL and those with CLL-RT.…”
Section: Introductionmentioning
confidence: 99%
“…OS and PFS appeared similar regardless of whether patients had received one versus two or more novel agents or a BTK versus a BCL2 inhibitor as the most recent line of therapy before allogeneic HCT. Encouragingly, both studies also reported low risks of TRM at 7% and 13% with modern transplantation techniques (100,120). It is conceivable that modern CLL therapies have the potential to improve the outcomes of allogeneic HCT by optimizing pretransplant disease control or by inducing less toxicity compared to conventional chemotherapy.…”
Section: Outcomes Of Allogeneic Hct For Cllmentioning
confidence: 98%
“…The cumulative incidence of relapse and non-relapse mortality (NRM) was 24% and 7%, respectively. The hematopoietic cell transplantation-specific comorbidity index (HCT-CI) was the only baseline clinical features (including HLA matching status, number and type of prior targeted inhibitors, and adverse genetic features) associated with an increased risk of death [hazard ratio (HR), 1.4; p=0.032] on univariable analysis ( 56 ).…”
Section: Allosct For Cll In the Targeted Inhibitor Eramentioning
confidence: 99%